First record of a fin whale (Balaenoptera physalus) in coastal waters of Ecuador in a century - Felix, Fernando; Haase, Ben; Teran, Claudia; Pozo, Miguel; Burneo, Santiago (J. Cetacean Res. Manage., 2022)
A male 16.9m fin whale (Balaenoptera physalus) was stranded on 3 April 2019 at Chanduy southwestern Ecuador (2°23’29.4” S, 80°44’17.96” W). Its coloration pattern, including the white-colored right side of the mouth and around 200 cream-colored baleens, are characteristics of the species. This is the first confirmed record of the species in almost a century in mainland Ecuador. A skin sample was taken for molecular studies. Fragments of the D-loop and CytB mitochondrial genes were amplified and compared with global databases. The D-loop fragment matched with a haplotype found in a fin whale from the Central-south of Chile and the CytB with several populations in both hemispheres. Our findings confirm that the Ecuadorian coast is part of the distribution area of southeastern Pacific fin whales.